SISTEM INFORMASI MANAJEMEN PENJUALAN SEMBAKO PADA TOKO JAYAPRATAMA ABEPURA - Heru Sutejo; Gracella Bakarbesy Paiki (ADISAM PUBLISHER, 2025)
This research aims to design a Sales Management Information System (SIM) specifically for Toko Jayapratama Abepura, a retail store selling basic necessities. The system is designed using the Waterfall method, which includes the stages of requirement analysis, system design, implementation planning, testing, and documentation. The analysis focuses on system planning using Data Flow Diagrams (DFD) Level 0 and Level 1. The design outlines the flow of data between entities such as admin and cashier, along with system processes including login, data management, transaction handling, and report generation. This system is expected to improve the efficiency of sales transactions and inventory management, while reducing errors in manual processing. Although the system has not been implemented, the design provides a comprehensive blueprint for future development